Upaya Madrasah dalam Meningkatkan Hafalan Al-Qur’an terhadap Peserta Didik MI Terpadu Tahfidzul Qur’an Al-Ma’shum Surakarta (MITTQUM) - Kinesti, Rakanita Dyah Ayu; Santi, Laila Tiara; Bayhaqi, Ahmad Mawahib; Oktriani, Ranti (ANWARUL, 2023)
Memorization of the Qur'an is one of the important aspects of religious education in Madrasah Ibtidaiyah (MI) Tahfidzul Qur'an. This article aims to explain the efforts made by madrasas in increasing students' memorization of the Qur'an. The approach used includes the use of the Murojaah, Talqin, wahdah methods, the formation of a conducive learning environment, the application of motivational strategies, and close collaboration between madrasahs and parents. The implementation of these efforts aims to provide greater opportunities for MI Tahfidzul Qur'an students to memorize and understand the Qur'an well. Formation of a conducive learning environment is an important factor in increasing the memorization of the Qur'an. Madrasas create a supportive atmosphere, such as the use of a special room for tahfizh, the provision of adequate learning materials and facilities, as well as a structured schedule to optimize memorization time. In addition, madrasas also apply motivational strategies, such as giving awards to students who achieve achievements in memorizing the Qur'an. Through these efforts, the Madrasa MI Tahfidzul Qur'an is committed to increasing students' memorization of the Qur'an. The application of the Murojaah, Talqin, Wahdah methods, the formation of a conducive learning environment, motivational strategies, and close collaboration with parents are steps that play an important role in achieving this goal. With continuous efforts and continuous support, it is hoped that MI Tahfidzul Qur'an students can memorize the Qur'an properly and understand the messages contained in it.